1992
DOI: 10.1183/09031936.93.05040452
|View full text |Cite
|
Sign up to set email alerts
|

Continuous longitudinal regression equations for pulmonary function measures

Abstract: The data from a longitudinal population study in Tucson, Arizona, were used to describe the development and decline of maximal expiratory flow-volume (MEFV) measures with age. On the basis of their answers to self-administered questionnaires, in 9 of the first 10 surveys (1972-1988) and having performed at least one MEFV test, 930 nonsmoking healthy subjects were selected, providing 3,848 individual observations. The data were analysed using statistical methods that yield continuous piecewise linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Loss of alveolar elastic recoil results in increased residual volume and, as a consequence, reduced vital capacity. The reduction in forced vital capacity with age has been shown previously to be biphasic [27] and this is also indicated in our data based on NHANES subjects, with the accelerated decline starting a few years earlier in women than men. Also, the loss of static lung elastic recoil is primarily seen after age 59 years (men and women presented together), with almost no loss before that age [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Loss of alveolar elastic recoil results in increased residual volume and, as a consequence, reduced vital capacity. The reduction in forced vital capacity with age has been shown previously to be biphasic [27] and this is also indicated in our data based on NHANES subjects, with the accelerated decline starting a few years earlier in women than men. Also, the loss of static lung elastic recoil is primarily seen after age 59 years (men and women presented together), with almost no loss before that age [28].…”
Section: Discussionsupporting
confidence: 88%
“…The reduction in FVC throughout adulthood also appeared biphasic in this NHANES material, again with the breakpoint occurring earlier in females, though the breakpoint was not as clear in males as in females. Sherrill et al could also confirm a biphasic decline of FVC in women, with the breakpoint at 46 years, but could not detect any breakpoint in men using piecewise regression in a longitudinal study on 930 non-smoking healthy subjects [27]. In the same study, clear-cut breakpoints were identified in upper middle age for both women and men regarding the age-related decrease in mid-expiratory flows, whereas the reduction in FEV 1 was linear from approximately 25 years of age in this material.…”
Section: Discussionmentioning
confidence: 97%
“…The following pulmonary function indices were included in the analysis: forced vital capacity (FVC), forced expiratory volume in one second (FEV 1 ), and the ratio FEVJFVC. Percentage predicted values were computed using previously published reference equations [35,36].…”
mentioning
confidence: 99%